Increasing quantitative estrogen receptor beta expression in meningioma after exogenous hormonal contraception exposure - Dhimas Hari Sakti; Muhammad Bayu Sasongko; Suhardjo Pawiroranu; Didik Setyo Heriyanto; Indra Tri Mahayana; Datu Respatika; Idhayu Anggit Widhasari; Prima Sugesty Nurlaila; Agus Supartoto (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Factors influencing estrogen receptor (ER) and progesterone receptor (PR) expression in meningioma are unclear. This study aimed to assess the expression of ER and PR in females with meningioma in relation to patient exogenous hormonal exposure. Cross-sectional study of females with meningioma in Yogyakarta, Indonesia, between 2010 to 2016 was conducted. Histories were obtained through interviews. Expressions of ERa, ERb, and PR were assessed from paraffin blocks containing patients’ meningioma tissue using real-time quantitative polymerase chain reaction (RT-qPCR). The study identified 28 female meningioma patients with a mean age of 45.6 ± 6.8 yr. Increased ERb expression was found in the ³10-yr group of hormonal contraception exposure duration (<10 yr vs ³10 yr = 7.63 (2.3-11.31) vs 12.56 (1.87-42.22), p=0.038). Positive correlation was found between ERb expression and the duration of hormonal contraception exposure (r=0.432; p=0.022), especially progesterone-only contraception (r=0.5; p=0.048), while no significant correlation was found between ERb expression and duration of progesterone-estrogen contraception exposure (r=0.382; p=0.22). No significant analyses were found in ERa and PR. In conclusion, expression of ERβ in meningioma increased in accordance with exogenous hormonal exposure duration, especially progesterone. This finding suggests the importance of ERβ in meningioma and warrants further study as a potential biomarker.